Taxonomic revision of the New World genus Callotillus Wolcott (Cleridae, Tillinae), with the description of the new genus Neocallotillus, and an illustrated key of identification to species - Burke, Alan F.; Zolnerowich, Gregory (My University, 2016)
The New World checkered beetle genus Callotillus Wolcott, 1911 is revised and the new genus Neocallotillus established. The subspecies Callotillus elegans vafer Wolcott is synonymized with the nominal subspecies, C. elegans elegans (Erichson), which is transferred to, and designated as the type species of Neocallotillus gen. n. as Neocallotillus elegans (Erichson, 1847), comb. n. Two additional species are transferred from Callotillus to the new genus: Neocallotillus intricatus (Wolcott & Dybas, 1947), comb. n. and N. crusoe (Wolcott, 1923), comb. n., the latter tentatively and based on Wolcott’s original description. Callotillus is now composed of two species: C. eburneocinctus Wolcott, 1911 and C. bahamensis Vaurie, 1952. All abovementioned species except N. crusoe are diagnosed and redescribed. In the absence of reference material of Neocallotillus crusoe, Wolcott’s original description is transcribed. An illustrated key to species is provided. Characters of taxonomic relevance are illustrated and discussed. Updated distribution maps and locality data for all specimens examined are presented.
Citation: Burke AF, Zolnerowich G (2016) Taxonomic revision of the New World genus Callotillus Wolcott (Cleridae, Tillinae), with the description of the new genus Neocallotillus, and an illustrated key of identification to species. ZooKeys 617: 65–89. doi: 10.3897/zookeys.617.9970
Keywords: West Indies; North America; Central America; Geographic Range; Taxonomy